Uji Toksisitas Akut Limbah Cair Tahu Terhadap Daphnia Magna Dengan Metode Renewal Test - Floria Christin; Shinta Elystia; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Tofu is a domestic industry developed rapidly in indonesia. Unfortunately the treatment of wastewater has not been done before the wastewater is thrown away to receiving water bodies. Therefore it is one of the causes of water pollution that effect the death of aquatic biota. Thus it is needed to do acute toxicity test. The goal of the research are to know the value of LC50 and to analyze the relationship of industrial wastewater of tofu UD. Tahu Jaya towards the experimental animal. Acute toxicity test is done by renewal test method in 96 hours using Daphnia Magna. The characteristic consentration of wastewater of tofu UD. Tahu Jaya is COD 4750 mg/l, TSS 2100 mg/l, ammonia 5,29 mg/l, pH 3 and temperature 33°C. Based on the result of analysis characteristics of tofu wastewater, it is known that the parameters of COD, TSS, ammonia, pass the quality standart of the rules of Enviromental Ministry No. 15 Year 2008 about the Quality Standart of Waste Water for Industry and Soybean Processing Activity. The value of LC50 is 6,509% and TUa (Toxicity Unit Area) of tofu industrial wastewater is 15,36 showed that the wastewater of tofu is very cause acute toxicity.Keywords: daphnia magna, LC50-96 hours, renewal test, tofu wastewater